Determinants of Capital Structure Using Profitability as Moderating in Indonesia’s Property and Real Estate Firms - Tamba, Cecilia Anggie O.; Purwanto, Purwanto (Directorate of Academic Research and Community Services, 2021)
The research aim is to examine determinant factors of Indonesia's property and real estate firms capital structure listed in the Indonesia Stock Exchange. This is a quantitative research which taken 72 observation data from 12 companies audited financial statement and fulfilled certain criteria. Processing through classical assumption tests and multivariate analysis with the help of the EViews 10 software instrument. The results show that tangibility assets, business risk, and firm size have a significant influence on capital structure partially, but sales growth and liquidity have insignificant. The determination coefficient is 42.83% and the proportion is included in the strong criteria. Profitability as a moderating variable weakens the effect of business risk but strengthens the effect of firm size on the debt to equity ratio, further determining the company's ability to pay off its debt which is of great concern to investors and creditors. Furthermore, as a consideration for choosing the composition of a good funding decision in Indonesia.